Điều chế và tính chất của 5-(5-Axetamido-2-Hidroxiphenyl)-1,3,4-Oxadiazol-2-Thiol - Bôi, Lưu Văn; Sơn, Nguyễn Thị; Nhung, Đào Thị (VNU Journal of Science: Natural Sciences and Technology; Vol 24 No 1, 2008)
Abstract